The glittering hour - Grey, Iona (Thomas Dunne Books, 2019)
"An unforgettable historical about true love found and lost and the secrets we keep from one another from an award-winning author. Selina Lennox is a Bright Young Thing. Her life is a whirl of parties and drinking, pursued by the press and staying on just the right side of scandal, all while running from the life her parents would choose for her. Lawrence Weston is a penniless painter who stumbles into Selina's orbit one night and can never let her go even while knowing someone of her stature could never end up with someone of his. Except Selina falls hard for Lawrence, envisioning a life of true happiness. But when tragedy strikes, Selina finds herself choosing what's safe over what's right. Spanning two decades and a seismic shift in British history as World War II approaches, Iona Grey's The Glittering Hour is an epic novel of passion, heartache and loss"--